HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN DIET DIABETES PADA PASIEN DIABETES MELLITUS TIPE 2 DI WILAYAH PUSKESMAS LIMO DEPOK - Dayan Hisni; Retno Widowati; Nur Wahidin (Jurnal Ilmu dan Budaya, 2017)
Diabetes Mellitus (DM) is the metabolic and chronic diseases characterized by hyperglycemia resulting from a defect in the production of insulin, action of insulin or both. The prevalence of type 2 DM was increased rapidly including in Indonesia. In Depok City, 145 people lived with type 2 DM. One of the treatment for type 2 DM patient is Dietary Adherence. The effectiveness of the dietary adherence in patient with type 2 DM could be influenced by the family support. The aimed of the study was to identify the relationship between family support and dietary adherence in patient with type 2 DM at Limo Public Health Center, Depok. There were 60 patients with type 2 DM at Limo Public Health Center, Depok. A descriptive correlation with the cross sectional design was used. The Dietary Adherence Questionnaire and the Family Support Questionnaire were used to the data collection then chi-square was performed to analyzed the data. The results of the study revealed that there was a relationship between family support and dietary adherence in patients with type 2 DM at Limo Public Health Center, Depok (p<.05). The family support is one of the nursing intervention to improve the dietary adherence in patient with DM. Moreover, due to patients with type 2 DM were interacted with their family commonly therefore family support could be a motivation to improve the dietary adherence.